Collaborative Learning in Higher Education To Improve Employability: Opportunities and Challenges. Issue 163 (3rd September 2019) - Robbins, Stacey; Hoggan, Chad
Abstract: This chapter draws on research in organizational (workplace) learning to provide guidelines for educators to effectively design, facilitate, and evaluate collaborative learning experiences.